La influencia de la marca Starbucks en la percepción del valor del producto - Bazán Silva, Maria Paula (2021)
This research study aims to determine the influence of the Starbucks brand on the consumers perceived value of the product. In addition, it is intended to describe the brand identity that Starbucks transmits to its consumers and to determine the relationship between, specifically, brand satisfaction and brand loyalty with the perceived value of the brand's products. To do this, a quantitative approach methodology was used, collecting the required information through a questionnaire applied to a sample of 200 Starbucks consumers, between 18 and 55 years, from A and B socioeconomic levels, who reside in Zone 7 of Metropolitan Lima, Perú. The data treatment was carried out with the SPSS statistical program, through an analysis of descriptive statistics, contingency tables and correlations between the indicators that explain the study variables. The results obtained show that Starbucks brand exerts a direct and positive influence on the product´s perceived value; it also has a favorable brand identity in the consumers mind, and Starbucks brand satisfaction and loyalty have a direct and positive influence on the product´s perceived value.